2014
DOI: 10.1007/s12010-014-1250-2
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Extraction of Phycobiliproteins from Porphyridium purpureum

Abstract: In the present study, microwave-assisted extraction was first employed to extract the phycobiliproteins of Porphyridium purpureum (Pp). Freeze-dried Pp cells were subjected to microwave-assisted extraction (MAE) to extract phycoerythin (PE), phycocyanin (PC), and allophycocyanin (APC). MAE combined reproducibility and high extraction yields and allowed a 180- to 1,080-fold reduction of the extraction time compared to a conventional soaking process. The maximal PE extraction yield was obtained after 10-s MAE at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(36 citation statements)
references
References 40 publications
1
35
0
Order By: Relevance
“…As can be seen, higher C-PC content was obtained using distilled water as solvent, a power of 100 W for 30 s. Figure 1 represents standardized Pareto charts ( Figure 1A) where non-significant variables of the model were eliminated and the response surfaces on the basis of the factors selection ( Figure 1B where C-CP is C-phycocyanin content in mg/g, P: is power in W, t: is the extraction time in seconds, and S: is solvent type ( Table 3). This confirms what is described by Juin, et al [28] being that the overexposure to high heat (intense power) could damage the C-PC content in the extraction. In this way, our results showed that the C-PC content reached from A. maxima was higher than other results described in microalgal phycobiliproteins having~198.3 mg/g as the predicted optimal value by statistic software and~215.0 ± 5.5 mg/g as the real extracted content.…”
Section: Optimization Of Mw Extraction Conditions For C-pc From Arthrsupporting
confidence: 92%
“…As can be seen, higher C-PC content was obtained using distilled water as solvent, a power of 100 W for 30 s. Figure 1 represents standardized Pareto charts ( Figure 1A) where non-significant variables of the model were eliminated and the response surfaces on the basis of the factors selection ( Figure 1B where C-CP is C-phycocyanin content in mg/g, P: is power in W, t: is the extraction time in seconds, and S: is solvent type ( Table 3). This confirms what is described by Juin, et al [28] being that the overexposure to high heat (intense power) could damage the C-PC content in the extraction. In this way, our results showed that the C-PC content reached from A. maxima was higher than other results described in microalgal phycobiliproteins having~198.3 mg/g as the predicted optimal value by statistic software and~215.0 ± 5.5 mg/g as the real extracted content.…”
Section: Optimization Of Mw Extraction Conditions For C-pc From Arthrsupporting
confidence: 92%
“…Because of its hard cell wall that limits intracellular metabolites extractability, we optimized a microwave-assisted extraction (MAE) to obtain high pigments extraction yields using a fast process, as previously reported by our group [28,29]. Twenty mg freeze-dried Ht cells were suspended in 5 mL ethanol in 10 mL sealed glass vials under air.…”
Section: Microwave-assisted Extraction Of Ht Pigmentsmentioning
confidence: 99%
“…However, extraction from cyanobacteria is not simple due to their special multilayered cell wall and the presence of contaminants, therefore, extraction usually results either in high purity or high efficiency. Isolation consists typically of two phases: (1) liberation of intracellular content by pretreatment to yield a crude extract (i.e., by precipitation, centrifugation, or other treatments including microwave-or ultrasound-assisted extraction [75,76]), (2) isolation/purification step(s) that separate the pigment-protein complexes by conventional methods [5,13,61,73,[77][78][79][80][81]. Phycocyanin is mostly extracted from Arthrospira [79,[81][82][83] (Fig.…”
Section: Sources For Industrial Extractionmentioning
confidence: 99%
“…At the same time, the therapeutic potentials of phycobiliproteins and phycobilins were in general tested for phycocyanin and/or phycocyanobilin obtained from Spirulina, while phycobiliproteins and phycobilins (e.g., also allophycocyanin [255] and phycoerythrin [77,[85][86][87][88]90,164]) obtained from other cyanobacteria (e.g., Anabaena marina [92], Aphanizomenon flos-aquae [117], Limnothrix [173,174], Lyngbya [142], Myxosarcina concinna [255], Microcystis [122], Oscillatoria tenuis [151], Phormidium fragile [256], Phormidium tenue [139,142,201] or Pseudanabaena tenuis [204]) or red algae (Corallina elongata [86], Heterosiphonia japonica [87], Polysiphonia urceolata [85,88], Porphyra yezoensis [166], Porphyra haitanensis [164], Porphyridium purpureum [76] or Porphyridium cruentum [90]) and other species may also have similar (or other) potential, and thus, require further studies. Isolated peptides of phycocyanins may also have therapeutical potential as they had antioxidant activity and inhibited the ROS induced DNA damage in vitro [161].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%